2019
DOI: 10.21873/invivo.11561
|View full text |Cite
|
Sign up to set email alerts
|

A Phase I Study of Napabucasin Plus Paclitaxel for Japanese Patients With Advanced/Recurrent Gastric Cancer

Abstract: Aim: To report results from the first phase I study of napabucasin plus paclitaxel in Japanese patients with pretreated unresectable/recurrent gastric cancer. Patients and Methods: Patients received napabucasin (480 mg bid) plus paclitaxel [80 mg/m 2 on days 3, 10 and 17 (cycles 1 and 2) and on days 1, 8 and 15 (cycle 3 and subsequent cycles)] until disease progression or unacceptable toxicity. Primary objectives were tolerability, safety and pharmacokinetics of napabucasin plus paclitaxel. Trial registration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 18 publications
5
13
0
Order By: Relevance
“…In one of these patients, even after paclitaxel was discontinued at cycle 7, partial response was maintained until cycle 21 with napabucasin treatment alone. Collectively, this study demonstrates that drug combinations with napabucasin are a viable treatment approach with potential survival benefits and hence a Phase III trial is ongoing for this combination in gastric and gastroesophageal junction cancers (NCT02178956) [98]. In preclinical studies of HCC, napabucasin promoted apoptosis in vitro and suppressed tumor growth in orthotopic mouse models [104].…”
Section: Targeting Stat3mentioning
confidence: 91%
See 1 more Smart Citation
“…In one of these patients, even after paclitaxel was discontinued at cycle 7, partial response was maintained until cycle 21 with napabucasin treatment alone. Collectively, this study demonstrates that drug combinations with napabucasin are a viable treatment approach with potential survival benefits and hence a Phase III trial is ongoing for this combination in gastric and gastroesophageal junction cancers (NCT02178956) [98]. In preclinical studies of HCC, napabucasin promoted apoptosis in vitro and suppressed tumor growth in orthotopic mouse models [104].…”
Section: Targeting Stat3mentioning
confidence: 91%
“…Napabucasin is a STAT3 inhibitor that has been found to have preliminary clinical efficacy. In a clinical trial of napabucasin combined with paclitaxel (JapicCTI-142420), the two drugs were shown to be well tolerated in Japanese patients with gastric cancer [98]. Common adverse effects reported were generally mild and gastrointestinal, but concurrent administration with loperamide was able to control these negative effects.…”
Section: Targeting Stat3mentioning
confidence: 99%
“…The small molecule napabucasin (BBI608) was identified as a STAT3 inhibitor that targets cancer stem cells 35 . Combination treatment with napabucasin and conventional chemotherapy is under evaluation in clinical trials, particularly for advanced cancer patients 42 (Table 2).…”
Section: Clinical Evaluation Of Small Molecule Inhibitors Targeting Dmentioning
confidence: 99%
“…Napabucasin exerts its antitumor activity by increasing levels of ROS beyond a cytotoxic threshold, causing cancer cell death 1–3 . Treatment of several cancers with napabucasin alone or in combination with other cancer therapies has been assessed in a number of ongoing clinical trials (congress abstracts, 4–16 and completed clinical trials 17,18 ). An ongoing phase 3 study is assessing napabucasin in combination with 5‐fluorouracil, leucovorin, and irinotecan (i.e., FOLFIRI) in patients with previously treated metastatic colorectal cancer (Clinicaltrials.gov identifier: NCT02753127) 19 …”
Section: Introductionmentioning
confidence: 99%